Acute kidney injury due to direct infiltration by lymphoplasmacytic lymphoma secreting IgG paraproteins: A case report. Issue 24 (17th June 2022) - Kim, Seongmin; Bae, Wooram; Choi, Jungyoon; Lee, Tae Won; Song, Dae Hyun; Bae, Eunjin; Jang, Ha Nee; Chang, Se-Ho; Park, Dong Jun
Abstract: Introduction: Waldenström's macroglobulinemia is a lymphoplasmacytic lymphoma (LPL) associated with a monoclonal immunoglobulin M protein. Although acute kidney injury (AKI) due to immunoglobulin M paraprotein infiltration into the renal interstitium has been reported, there has been no report of AKI with invasion of the immunoglobulin G paraprotein into the renal interstitium in a patient with LPL. Patient concerns: A 65-year-old male was admitted to our hospital with fatigue and decreased renal function. He complained of a 3-kg weight loss in the last 3 months. Diagnosis: The initial blood urea nitrogen and serum creatinine levels were 55.9 and 1.83 mg/dL, respectively. Serum protein electrophoresis revealed a monoclonal component (3.5 g/dL) in the gamma region and immunofixation electrophoresis showed an immunoglobulin G kappa monoclonal protein. Renal pathology revealed that CD3–CD20+ CD138+ lymphoid cells had infiltrated the renal interstitium. A bone marrow biopsy was compatible with LPL. Interventions: Intravenous methylprednisolone (1 mg/kg) was administered after confirming the renal pathological findings. Outcomes: Serum creatinine decreased to 0.8 mg/dL 14 days after treatment Conclusions: Physicians should recognize LPL secreting various immunoglobulins as a possible cause of AKI when renal failure of unknown etiology and serum immunoglobulin paraprotein is present. A kidney biopsy should be performed for definitive diagnosis and appropriate management.